The impact of extrinsic factors on the personal attitude of agricultural students’ to start a new farming venture - Mbulaheni Mavhungu (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The study aimed to determine the impact of extrinsic business start-up factors on personal attitude of agricultural students’ to start a new venture in South Africa. An estimated 3,486 students were enrolled for various agriculture-related qualifications in various institutions of higher learning in South Africa when this cross-sectional, quantitative study was carried out. Data of 421 agricultural students were collected through a Prospective Farmers Profile Questionnaire at six universities in South Africa. Through regression model and Pearson correlations, SPSS was used to analyse data. The results showed a significant relationship between personal attitude and human capital and skills of agricultural students to start a new farming venture. The findings revealed that no significant relationship between personal attitude and access to land as well as political skills of agricultural students to start a new farming venture, while actually access to land and political skills are the most important factors for entrepreneurship but agricultural students do not consider them important. Therefore, agricultural students should be orientated to these factors and their role in entrepreneurship through entrepreneurial education. Agricultural sector may take an initiative and educate students through different platforms to familiarise them with the role that these factors may play in entrepreneurship.